Tetrahedral framework nucleic acids facilitate neurorestoration of facial nerves by activating the NGF/PI3K/AKT pathway. Issue 37 (16th September 2021) - Yao, Yangxue; Wen, Yuting; Li, Yanjing; Zhu, Jianwei; Tian, Taoran; Zhang, Qi; Xiao, Dexuan; Gao, Yang; Lin, Yunfeng; Wei, Wei; Cai, Xiaoxiao
Abstract : tFNAs to be applied in the therapy of facial nerve injury or even peripheral nerve injury. Abstract : The facial nerve is a crucial nerve in the maxillofacial region and is vulnerable to damage. As a consequence of the complications during nerve restoration, existing remedies have certain limitations, thus the treatment of facial nerve injury is always a perplexing task for people. Regulation of Schwann cells is always the breakpoint of neurorestoration since Schwann cells count a great deal in injured nerve repair. In this study, we presented proof that tetrahedral framework nucleic acids (tFNAs), a kind of nucleic acid nanomaterial, were capable of regulating the neurorestorative pathway NGF/PI3 K/AKT, resulting in the activation of a series of cell behaviors related to injured nerve restoration such as proliferation and migration. In vivo experiments also proved that tFNAs enhanced the expressions of axon and myelin marker proteins, impelled histological recovery, promoted the efficient restoration of nerve conduction and muscle movement. Additionally, tFNAs possessed excellent biocompatibility and superior endocytosis ability. Thus, there is good potential for tFNAs to be applied in the therapy of facial nerve injury or even peripheral nerve injury.